Personal Tax Changes and Financial Well-Being: Evidence from the Tax Cuts and Jobs Act - Christine L. Dobridge; Joanne Hsu; Mike Zabek (CESifo GmbH, 2025)
We estimate the effects of personal income tax decreases on financial well-being, including qualitative subjective assessments and quantitative measures. A plausibly causal design shows that tax decreases in the Tax Cuts and Jobs Act made survey respondents more likely to say they were "living comfortably" financially, with null effects at lower levels of subjective financial well-being. Estimates from a similar design using credit bureau data show that people who had larger tax decreases were modestly more likely to open new accounts and more likely to have higher consumer credit balances. Tax decreases had effects on credit scores and delinquencies that are indistinguishable from zero. Results suggest that larger tax decreases improve financial well-being in ways not fully proxied by typical administrative data.
Keywords: H24; G50; I31; 330; taxes; subjective well-being; household finances; credit; financial well-being